Collaborative Governance Model in Strengthening the Competitiveness of Leading Commodities to Support Food Security and Independence - Joubert M. Dame; Arsana, I Kadek Satria (Sean Institute, 2025)
This study develops a collaborative governance model to strengthen the competitiveness of leading commodities in Sangihe Islands Regency in support of national food security and sovereignty. Employing a mixed-methods design, the research integrates quantitative tools (Location Quotient, IFAS–EFAS, SWOT) with qualitative approaches (interviews, focus group discussions, and participatory observation). The results identify pig farming as the foremost leading commodity, followed by native chicken and duck eggs, while cattle and broiler chickens remain in need of further development. Structural constraints include weak logistics, limited human resources, and dependence on imported feed. To overcome these challenges, the proposed model fosters multi-stakeholder collaboration involving local government, farmers, the private sector, and academia, reinforced by digital platforms, financing schemes, and quality control systems. The roadmap emphasises synergy between local wisdom (Mapalus) and digital innovation to enhance competitiveness, alleviate poverty, and bolster regional contributions to national food resilience.